Description of meta-analysis of science learning through inquiry model in improving students' science process skills - H Miranti; Abdurrahman Abdurrahman; C Ertikanto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This meta-analysis was the result of the preliminary study aimed to descript the analysis of science learning through inquiry model in improving students' science process skills. This study analyzed ten national research journals and five international journals. Analysis of data used a description of the results of the average effect size (ES) of any studies that were sampled, and then categorized based on the interpretation of the criteria Cohen's. The results showed that science learning which was conducting through inquiry model can improve students' science process skill which was indicated by the average effect size of 0.51 with category "medium". Based on the criteria Cohen's also analyzed about the differences in science process skills based on group of countries, fields of study, and levels of education. The results of this study can be concluded that inquiry-based learning can be applied to the development of science learning in order to grow students' science process skills.